2002
DOI: 10.1002/ijc.10237
|View full text |Cite
|
Sign up to set email alerts
|

Testing mouse mammary tumor virus superantigen as adjuvant in cytotoxic T‐lymphocyte responses against a melanoma tumor antigen

Abstract: Cytotoxic T cells represent a powerful strategy for antitumor treatment. Depending on the route of injection, an important role for CD4 T cell-mediated help was observed in the induction of this response. For this reason, we investigated whether induction of a CTL response to the HLA-A2-restricted immunodominant peptide melanoma antigen Melan-A was improved by using rVVs expressing the CTLdefined epitope alone or in combination with an SAg. In the latter case, the few infected dendritic cells simultaneously pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…20) This effect has been extensively utilized for antitumor immunotherapy. [21][22][23][24][25][26][27][28] Our previous studies showed that SAgs could produce better efficacy when combined with other methods, such as genetically introduced cytokines. [29][30][31] Therefore, we wondered if SAg activation could be utilized to potentiate HSPs' antitumor-specific immunity, and we hypothesized that SAg anchored on vaccine cells transduced with HSP gene might locally break immune tolerance and cause immune-activation around the cells.…”
mentioning
confidence: 99%
“…20) This effect has been extensively utilized for antitumor immunotherapy. [21][22][23][24][25][26][27][28] Our previous studies showed that SAgs could produce better efficacy when combined with other methods, such as genetically introduced cytokines. [29][30][31] Therefore, we wondered if SAg activation could be utilized to potentiate HSPs' antitumor-specific immunity, and we hypothesized that SAg anchored on vaccine cells transduced with HSP gene might locally break immune tolerance and cause immune-activation around the cells.…”
mentioning
confidence: 99%
“…This was also shown in chickens vaccinated with an inactivated avian influenza vaccine added with 20 µg of a recombinant N protein expressed in baculovirus (N-Bac), analyzing the expression of mRNA by RT/PCR (Loza-Rubio et al 2002). Recently, some reports have recognized superantigens as immunomodulators and adjuvants, and their role in protection (Papageorgiou and Acharya 1997;Okamoto et al 2001;Loza-Rubio 2003;Wirth et al 2002;McAleer et al 2007;Miles et al 2008).…”
Section: Discussionmentioning
confidence: 99%